Meta-analysis and GRADE evidence evaluation of acupuncture in the treatment of type 2 diabetes mellitus - CHEN Jun-tao*, CHEN Tian-wei, FENG Yuan-hui, YANG Yi-chen, ZHOU Zi-xian, LI Rui, MA Hui-fang (Zhongguo linchuang yanjiu, 2023)
Objective To systematically evaluate the clinical efficacy of acupuncture in the treatment of type 2 diabetes mellitus. Methods The related literatures of 12 databases at home and abroad were searched for the period from the establishment of the database to March 2022. RevMan 5.3 software was used for Meta-analysis. Results A total of 14 randomized controlled trials were included, including 1 344 patients. The results of Meta-analysis showed that acupuncture plus western medicine was superior to western medicine in improving fasting blood glucose［MD=-1.26, 95%CI（-1.50，-1.03）, Z=10.57, P＜0.01］, 2-hour postprandial blood glucose［MD=-1.65, 95%CI（-1.88，-1.42）,Z=14.25, P＜0.01］, glycosylated hemoglobin［MD=-0.97，95%CI（-1.25，-0.69）, Z=6.76, P＜0.01］ and insulin resistance index［MD=-1.35, 95%CI（-1.54，-1.15）, Z=13.23, P＜0.01］. GRADE evidence quality evaluation results showed that 2-hour postprandial blood glucose was high quality evidence, while fasting blood glucose, glycosylated hemoglobin and insulin resistance index were medium quality evidence. Conclusion The current evidence shows that the efficacy of acupuncture plus western medicine in the treatment of type 2 diabetes mellitus is better than that of western medicine. Acupuncture has a better effect on type 2 diabetes mellitus.